The implementation of learning writing and development of character values of high school students - Budiyono, Herman; Suroso, Suroso; Priyanto, Priyanto (LPMPP Universitas Negeri Yogyakarta, 2024)
This study aims to examine and describe the implementation of the stages of the learning writing process and the development of character values for senior high school students. The descriptive qualitative approach was used in the present study. The process of learning to write and developing student character values was analyzed and described. Data analysis steps include data reduction, data presentation, and drawing conclusions. The results of the research show that learning to write and develop students' character values is carried out in such stages as the context development stage (introduction), model review (core), and inference learning (closing). The characters fostered in learning include religiosity, discipline, curiosity, diligence, honesty, a love for reading, creativity, friendliness or communication skills, democracy, tolerance, independence, and responsibility.